Children’s Microsystems and Their Relationship to Stress and Executive Functioning - Campos-Gil, Jose Antonio; Ortega-Andeane, Patricia; Vargas, Delfino (Frontiers in Psychology, 2020)
Microsystems are described as contexts formed by a subject, their roles, interactions, and a specific physical space and time, such as housing and the school environment. Although several studies suggest the importance of studying this type of environment and its repercussion on children's development, in a Latin American context few studies integrate the interaction of two primary settings in the development of executive functioning. The present study explores the effects of the quality of housing and school environments on the perception of stress, decision making, and planning among children. A total of 114 children (43% girls and 57% boys, Mage = 10.57) from a primary school located in a community classified as poor participated in the study. It was measured: environmental quality of classrooms, housing, stress and executive functioning of children. The results reveal a model linking environmental quality levels in children's homes and schools and executive functioning. We also obtain a mediating role of stress between microsystems and performance, finding a deficit in executive performance when children experienced higher levels of stress as a result of poor environmental quality both in their homes and in their schools.